CuInxGa1-xS2 absorber material for thin-film solar cells - Pradeepkumar M.S.; Ahmad M.I. (My University, 2025)
Solar energy is an important component for fulfilling the growing energy demand. Solar cells are utilized to convert radiative solar energy into electrical energy. Silicon-based solar cells dominate the solar cell industry with a 92% market share. The Si-solar cells use 250–400 µm-thick Si wafer, making the solar cell heavy and nonflexible. At the same time, the processing of Si wafers is cost-intensive. Therefore alternative material systems that can be deposited as flexible thin films with cheaper processing routes are sought after. Thin-film solar cells were first demonstrated with copper sulfide as absorber material. Since then, several sulfide, selenide, and phosphide-based ceramic absorber materials have been developed. Presently, ceramic CuInGa(S, Se)2 absorber-based thin-film solar cells rival the performance of Si-solar cells with power conversion efficiency ~24%. The proposed chapter discusses the evolution of ceramic-based sulfide/selenide thin-film absorber materials and their structural, defect, and optical properties. This chapter also briefly describes various processing methods, their performance as solar cells, and strategies to improve performance. © 2023 Elsevier Ltd. All rights reserved.